The Affective and Cognitive Dimension: Evaluating Students’ Receptivity to Gamified Online Assesment - Neni Afrida Sari Harahap; Steven Ooan Siregar (Invention: Journal Research and Education Studies, 2026)
This study aims to investigate students’ attitudes toward the use of gamified online quizzes as authentic assessment in learning descriptive writing at MTsN 2 Medan. The research focuses on the affective and cognitive dimensions of students’ receptivity to digital assessment tools. The data are collected from 10 students selected through purposive sampling, as they have prior experience using online quizzes in English learning. This study employs a qualitative descriptive design. The data are gathered using a structured questionnaire distributed through Google Forms, consisting of Likert-scale and open-ended questions. The data analysis applies qualitative procedures including data reduction, data display, and conclusion drawing to identify patterns in students’ responses.The findings reveal that students show a generally positive attitude toward gamified online quizzes. In the affective dimension, most students feel motivated, excited, and more engagedcompared to traditional assessments. In the cognitive dimension, students believe that online quizzes help them understand descriptive text structures and language features more effectively, especially through immediate feedback. However, several challenges are identified, including internet instability and time pressure, which may influence students’ performance and confidence.The study implies that gamified online quizzes can serve as effective authentic assessment tools when supported by proper technical conditions. Teachers are encouraged to design flexible and meaningful digital assessments that balance engagement and accessibility to enhance students’ learning experiences.